Strategies for Scaling Micro-Affections to Sustain Long-Term Bonding: A Qualitative Study of Hungarian Couples - Conti, Marco; Kovács, Eszter (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study aimed to explore and conceptualize the everyday strategies couples use to scale micro-affections—small, intentional acts of love and care—in order to sustain emotional closeness and long-term relational stability.Methods and Materials: A qualitative design with an exploratory, interpretive approach was employed. Twenty Hungarian participants (10 couples) in long-term romantic relationships, ranging from 5 to 22 years, were selected through purposive sampling. Semi-structured, in-depth interviews were conducted until theoretical saturation was reached. The interviews, lasting 60–90 minutes, explored couples’ practices for maintaining connection, emotional safety, and adapting to life transitions. Data were audio-recorded, transcribed verbatim, and analyzed using a thematic approach supported by NVivo 14. Open, axial, and selective coding were applied to generate categories and subcategories, while constant comparison, memo writing, and member checking enhanced analytic rigor and trustworthiness.Findings: Three overarching themes emerged: nurturing everyday connection, sustaining emotional safety, and adaptive relationship growth. Couples sustained closeness through daily affectionate rituals, creative micro-gestures, and symbolic tokens of care. Emotional security was reinforced by responsive support, mutual vulnerability, quick conflict repair, gratitude, and respectful autonomy. Adaptive growth was maintained by updating love languages, co-creating future visions, sustaining playfulness, and integrating cultural traditions into evolving relational narratives. These strategies functioned as protective mechanisms against emotional distance and relational stagnation, enabling couples to maintain satisfaction despite external pressures and life transitions.Conclusion: The findings demonstrate that sustaining long-term romantic stability relies on the intentional, iterative use of small-scale affectionate behaviors embedded within a safe and adaptive relational climate. Understanding these lived strategies enriches theoretical models of marital maintenance and provides culturally informed, actionable insights for couple therapy, relationship education, and prevention of disaffection.